Labrador Sea freshening at 8.5 ka BP caused by Hudson Bay Ice Saddle collapse - Annalena Antonia Lochte (Nature Portfolio, 2019)
The exact freshwater scenario that caused the 8.2 ka cold event is still debated. This study presents new evidence for a severe Labrador shelfwater freshening 8500 years ago that was caused by the Hudson Bay Ice Saddle collapse following a warming in subsurface waters.